Legal Protection Against Creditors On Execution Of Land And Buildings According To Civil Law Perspectives (Decision Study No. 355/Pdt.G/2023/PN.Medan) - Rizka Putri Febritama; Dina Andiza; Mochammad Erwin Radityo (International Journal of Society and Law, 2024)
The execution of assets by creditors often raises disputes, especially in terms of debtors' rights that are not always well protected. Civil Law regulates the contractual relationship between the Creditor and the Debtor, but in the execution of execution, it is often found that the rights of the Debtor are neglected, especially in the execution of Land and Buildings which are important assets for the Debtor. There are three problems discussed in this Journal, namely, (1) What is the general view of Land and Buildings in Indonesia?, (2) What are the factors that cause Land and Buildings to be executed according to Civil Law? and (3) How to legally protect creditors for the execution of Land and Buildings according to the perspective of Civil Law based on Decision No.355/Pdt.G/2023/PN. Terrain. The type of research is Normative Law, with the nature of Analytical Descriptive Research, The research method used is literature research or document study. The types of data used are primary data and secondary data. In the perspective of Civil Law, the relationship between the Creditor and the Debtor is contractual, where both parties have rights and obligations regulated by the Laws and agreements.Enforcement regulations in the Civil Law in Indonesia need to be strengthened to prevent abuse of rights by creditors, as well as to protect the rights of debtors, especially in terms of land and building execution.